The melancholy void : lyric and masculinity in the age of Góngora - Valencia, Felipe, 1983- (New hispanisms., 2021)
Felipe Valencia examines the construction of lyric as a melancholy and masculinist discourse that sings of and perpetrates symbolic violence against the feminine and the female beloved in key texts of Spanish poetry from 1580 to 1620.